Academic Leadership and Vocational Training at the Public University - Cuentas Vargas, Sergio (2006)
The function of academic leadership, which implies research and preparation of the future intellectual elite connected to a broad vision of national development, and on the other hand, the function of training professionals for a specific market, taking into account its changing demands, are examined in this article, within the framework of a projected new public administration in Peru and Latin America.